PERANCANGAN SISTEM APLIKASI AMAL MASJID ONLINE MENGGUNAKAN METODE EXTREME PROGRAMMING BERBASIS MOBILE DI MASJID JAMI’ NURUL IHSAN GANDUL - Abdul Mutolib; Ari Mulyoto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Mosque fund management is an important part in carrying out development activities, therefore charity originating from the community is very useful for the continuity of mosque management. In the current system, donors set aside part of their sustenance by coming directly to the mosque manager, who then records all charitable income into the financial book. Based on these observations, the author tries to create an online mosque charity application using the mobile-based extreme programming method at the Jami' Nurul Ihsan Mosque, Gandul. This application is made using the PHP programming language because it is more flexible, easy to develop and easy to access. The database used uses MySQL because the security system is more secure. The purpose of making this application can help donors to do charity without coming to the mosque, can find out about religious activities, and mosque managers can list donors who do charity without writing in the financial book.